2020
DOI: 10.1136/bmjresp-2020-000569
|View full text |Cite
|
Sign up to set email alerts
|

Utility and validity of dynamic chest radiography in cystic fibrosis (dynamic CF): an observational, non-controlled, non-randomised, single-centre, prospective study

Abstract: IntroductionDynamic chest radiography (DCR) uses novel, low-dose radiographic technology to capture images of the thoracic cavity while in motion. Pulmonary function testing is important in cystic fibrosis (CF). The tolerability, rapid acquisition and lower radiation and cost compared with CT imaging may make DCR a useful adjunct to current standards of care.Methods and analysisThis is an observational, non-controlled, non-randomised, single-centre, prospective study. This study is conducted at the Liverpool H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…DCR can provide information on several points, such as pulmonary ventilation, diaphragm movement, and lung circulation (9)(10)(11). It is expected to be clinically applied in various fields, and some reports have already been published, describing DCR as useful for evaluating chronic obstructive pulmonary disease and cystic fibrosis patients (1,2,(12)(13)(14), in the clinical application of ventilation and perfusion (15,16), and for diagnosing pulmonary hypertension (5). However, there have been few reports of its surgical application, and the ones in existence are only case reports of surgery for pleural tumor (6).…”
Section: Discussionmentioning
confidence: 99%
“…DCR can provide information on several points, such as pulmonary ventilation, diaphragm movement, and lung circulation (9)(10)(11). It is expected to be clinically applied in various fields, and some reports have already been published, describing DCR as useful for evaluating chronic obstructive pulmonary disease and cystic fibrosis patients (1,2,(12)(13)(14), in the clinical application of ventilation and perfusion (15,16), and for diagnosing pulmonary hypertension (5). However, there have been few reports of its surgical application, and the ones in existence are only case reports of surgery for pleural tumor (6).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic chest radiography (DCR) is a novel imaging technology that makes use of a high-sensitivity flat panel detector with a large field of view to obtain successive radiographs (up to 15 images per second) thereby providing real-time images of the moving chest over 10–20 s [25 ▪ ]. In addition to providing structural information on the lungs, it can provide functional information on lung compliance and breathing patterns.…”
Section: Reviewmentioning
confidence: 99%
“…It can also calculate lung volumes by acquiring both PA and lateral projections. It has a relatively low radiation dose, with an average ED of 0.125 mSv [25 ▪ ]. DCR therefore offers a potential alternative means of assessing both pulmonary structure and function in CF.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…DCR provides a large amount of functional information on rib and diaphragm motion, cardiac motion, pulmonary ventilation, and perfusion. Several studies have reported potential clinical use for DCR (21)(22)(23)(24)(25)(26)(27)(28), focusing on motion analysis of lung structures. Notably, pulmonary ventilation and perfusion are reflected as time changes in radiographic lung density on DCR images.…”
Section: Introductionmentioning
confidence: 99%